COMPARISON OF HINT WIND TINES OF AIRFOIL TYPE NACA 4412, NACA 23012, and NACA 16-212 USING QBLADE SOFTWARE - Nurcholish Arifin Handoyono; Abdul Ghofur Syamdatu Wardhana (Universitas Sultan Ageng Tirtayasa, 2019)
Wind energy as one of the new renewable energies that has considerable potential in Indonesia is known by the rapid development of wind power plants in Indonesia. The windmill blade which is one of the main components of the windmill has a role as the conversion of wind potential energy into motion energy to eventually become electrical energy that is influenced by the shape of the windmill blade of the windmill. NACA (National Aeronautical Committee Advisory) in charge of aeronautics has standards regarding varying airfoil shapes. A comparison of variations of 4-digit type airfoils (NACA 4412), 5 digits (NACA 23012) and series 16 (NACA 16-212) to determine the value of Cl / Cd from the variation of NACA airfoil types. The results of simulations carried out using Qblade software showed that the value of Cl / Cd to the highest alpha of the three types of airfoils was NACA 4412 with a value of 134, alpha 6 and the Cp value for the highest TSR was 0.44 at TSR 5.5. Furthermore, the NACA 4412 airfoil blades can be developed by making lighter material variations so that the windmill blades are easier to spin so that the resulting power becomes more maximal.